Interhemispheric gradient of atmospheric radiocarbon reveals natural variability of Southern Ocean winds - Rodgers, Keith B.; Mikaloff-Fletcher, Sarah E.; Bianchi, Daniele; Beaulieu, Claudie; Galbraith, Eric D.; Gnanadesikan, Anand; Hogg, Alan G.; Iudicone, Daniele; Lintner, Benjamin R.; Naegler, Tobias; Reimer, Paula J.; Sarmiento, Jorge L.; et al. (Climate of the Past, 2011)
Tree ring Delta14C data indicate that atmospheric Delta14C varied on multi-decadal to centennial timescales, in both hemispheres, over the period between AD950 and 1830. The Northern and Southern Hemispheric Delta14C records display similar variability, but from the data alone is it not clear whether these variations are driven by the production of 14C in the stratosphere or by perturbations to exchanges between carbon reservoirs. As the sea-air flux of 14CO2 has a clear maximum in the open ocean regions of the Southern Ocean, relatively modest perturbations to the winds over this region drive significant perturbations to the interhemispheric gradient. In this study, model simulations are used to show that Southern Ocean winds are likely a main driver of the observed variability in the interhemispheric gradient over AD950–1830, and further, that this variability may be larger than the Southern Ocean wind trends that have been reported for recent decades (notably 1980–2004). This interpretation also implies that there may have been a significant weakening of the winds over the Southern Ocean within a few decades of AD1375, associated with the transition between the Medieval Climate Anomaly. (krodgers@princeton.edu) and the Little Ice Age. The driving forces that could have produced such a shift in the winds at the Medieval Climate Anomaly to Little Ice Age transition remain unknown. Our process-focused suite of perturbation experiments with models raises the possibility that the current generation of coupled climate and earth system models may underestimate the natural background multi-decadal- to centennial-timescale variations in the winds over the Southern Ocean.